Assessing Investment Risk in the Post-Pandemic Entertainment Industry: A Statistical Analysis of Portfolio Returns and Risk Measures - Ahmar, Ansari Saleh; Alsa, Yudhistira Ananda; Alfairus, Muh. Qodri; Rahman, Abdul; Kumar, Rajesh (Quantitative Economics and Management Studies, 2025)
This study examines the risk-return profiles of Warner Bros and Walt Disney stocks and analyzes their portfolio optimization potential in the post-pandemic entertainment industry landscape. Using daily stock data obtained from Yahoo Finance, we employ both traditional statistical analysis and Monte Carlo simulation techniques to derive robust estimates of expected returns and risk parameters. Our Value at Risk (VaR) analysis at multiple confidence levels (99%, 95%, and 90%) reveals distinct risk characteristics between the two stocks, with Walt Disney demonstrating more favorable downside protection despite similar historical return patterns. Monte Carlo simulations indicate significantly higher potential returns than suggested by historical data alone, with expected daily returns of 0.803% for Warner Bros and 0.789% for Walt Disney. Portfolio analysis with varying asset allocations demonstrates meaningful diversification benefits despite the substantial correlation (0.657) between the stocks. The optimal portfolio allocation favors a higher weight to Walt Disney (80%) compared to Warner Bros (20%), achieving the highest Sharpe ratio (0.247) and the lowest VaR at 99% confidence (-6.68%). These findings highlight the importance of comprehensive risk assessment tools in portfolio construction, particularly for industries undergoing structural transformation. The study contributes to sector-specific portfolio analysis literature by providing detailed insights into risk-return dynamics of major entertainment stocks in the evolving digital media landscape. For investors seeking entertainment sector exposure, our analysis suggests that a portfolio tilted toward Walt Disney offers the most efficient risk-return profile under current market conditions, though ongoing monitoring remains essential as business models continue to evolve.